Breast Reconstruction With Local Flaps: Don't Forget Grandma - Vivace, Bradley J. (Eplasty, 2019)
Objective: Lateral breast defects of various causes can be reconstructed with random patterned local flaps utilizing oncoplastic techniques. These local flaps are used frequently in other areas but are infrequent in breast reconstruction despite affording excellent utility in small lateral defects. We sought to demonstrate this with a case series involving 5 patients who underwent oncoplastic breast surgery with random patterned flap reconstruction. Methods: From 2016 to 2017, 3 different varieties of random flaps were used in 5 women requiring lateral breast defect reconstruction secondary to resection of localized cancer or cutaneous lesion. The local flaps included a rhomboid flap, the bilobed flap, and a rotational flap. Patients were then evaluated in the clinic 10 to 12 months postoperatively for complications, symmetry, and satisfaction of reconstruction. Results: In 4 of 5 patients, the local flap remained fully viable and there was no incidence of seroma, infection, or further complications. One patient developed a post-operative hematoma requiring evacuation and a second patient experienced distal flap necrosis and delayed wound healing. Patients reported satisfaction with the reconstruction. Conclusions: Several random patterned local flaps exist for a variety of breast defects. They can yield excellent cosmetic results, high patient satisfaction, and bolster a low rate of complications. Our case series emphasizes the utility of random patterned flaps for lateral breast oncoplastic reconstruction.